2008
DOI: 10.1111/j.1365-2893.2007.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

A phase II dose finding study of darbepoetin alpha and filgrastim for the management of anaemia and neutropenia in chronic hepatitis C treatment

Abstract: Dose reductions of pegylated interferon alpha and ribavirin may be avoided by using growth factors. This phase II clinical trial assesses the dose, efficacy and safety of darbepoetin alpha and filgrastim for treatment of anaemia and neutropenia associated with combination therapy for hepatitis C virus (HCV). Chronic hepatitis C patients (n = 101) received pegylated interferon alpha-2b (1.5 mug/kg once weekly) and ribavirin (800-1400 mg once daily). Patients with anaemia [haemoglobin (Hb) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 21 publications
3
35
0
Order By: Relevance
“…The results of previous studies [27,28,30,37,49,50,52,[56][57][58] and the present study have shown that the introduction of Epoetin Alpha therapy in patients treated with PEG-interferon alpha-2A and RBV for CH related to genotype 1b HCV infection leads to an improved adherence to treatment, and, consequently, to a significant improvement of SVR.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The results of previous studies [27,28,30,37,49,50,52,[56][57][58] and the present study have shown that the introduction of Epoetin Alpha therapy in patients treated with PEG-interferon alpha-2A and RBV for CH related to genotype 1b HCV infection leads to an improved adherence to treatment, and, consequently, to a significant improvement of SVR.…”
Section: Discussionsupporting
confidence: 56%
“…However, some studies have used decision analysis to estimate the cost-effectiveness of adjunctive therapy with erythropoietic growth factor (EGF) compared with that of standard care in the treatment of hepatitis C. The use of EGFs appears to be costeffective in patients with anaemia who are receiving combination therapy for HCV genotype 1, 2 or 3. Compared with The results of previous studies [27,28,30,37,49,50,52,[56][57][58] and the present study have shown that the introduction of Epoetin Alpha therapy in patients treated with PEG-interferon alpha-2A and RBV for CH related to genotype 1b HCV infection leads to an improved adherence to treatment, and, consequently, to a significant improvement of SVR.…”
Section: Resultssupporting
confidence: 41%
“…In our study, two of four patients in whom peginterferon dose was reduced before 12th week of treatment suffered a relapse after stopping peginterferon and ribavirin. Unfortunately, the use of granulocyte-colony-stimulating factors has shown contradictory results [13,14]. New studies are needed to evaluate the safety and efficacy of lowering neutrophil thresholds for reducing the dose of peginterferon.…”
Section: Discussionmentioning
confidence: 96%
“…[52][53][54][55][56][57][58][59] Two of the articles were abstracts 57,58 linked to full publications. 53,60 All of the included studies report peginterferon and ribavirin combination therapy in patients eligible for shortened treatment duration (i.e. those with specific genotypes as described in Chapter 3, Inclusion crtieria).…”
Section: Quantity and Quality Of Research Availablementioning
confidence: 99%